2022
DOI: 10.1016/j.cmi.2022.01.020
|View full text |Cite
|
Sign up to set email alerts
|

Predictors and microbiology of respiratory and bloodstream bacterial infection in patients with COVID-19: author's response

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 8 publications
(8 reference statements)
0
3
0
Order By: Relevance
“…The species involved in community-acquired superinfections are not different from those recovered from patients not infected with SARS-CoV-2. S. aureus and Haemophilus influenzae are the most frequent species recovered from patients at hospital admission [1,3,26]. Streptococcus pneumoniae seems to be less frequent comparatively with patients infected with the influenza virus [67], whereas Enterobacterales and S. aureus are the most frequent species involved in the case of secondary infection [26,68].…”
Section: Pneumonia In Non-invasively Ventilated Patientsmentioning
confidence: 99%
See 2 more Smart Citations
“…The species involved in community-acquired superinfections are not different from those recovered from patients not infected with SARS-CoV-2. S. aureus and Haemophilus influenzae are the most frequent species recovered from patients at hospital admission [1,3,26]. Streptococcus pneumoniae seems to be less frequent comparatively with patients infected with the influenza virus [67], whereas Enterobacterales and S. aureus are the most frequent species involved in the case of secondary infection [26,68].…”
Section: Pneumonia In Non-invasively Ventilated Patientsmentioning
confidence: 99%
“…Patients hospitalized with SARS-CoV-2 infection are rarely infected at admission [24,25 ]. Numerous studies conducted during the pandemic suggested a prevalence of coinfections around 3-7% [1], reaching 28% in ICUadmitted patients [26]. Moreover, infections occur more frequently in ICU patients, especially in the case of mechanical ventilation [27].…”
Section: Specificity Related To the Pandemicmentioning
confidence: 99%
See 1 more Smart Citation